Experimental and numerical investigation on hydrodynamic response of buoy form spar under regular waves. (2nd January 2017) - Nallayarasu, S.; Kumar, N. Senthil
Abstract : Spar platforms are used for drilling, production, storage and offloading of oil in deep water. Spar with its deep draft and large inertia experience low heave and pitch motions in operating conditions. However, the heave motions can be large when encountered by long-period swells or near resonant period. The heave motion of the Spar platforms can be reduced by decreasing the water plane area, increasing the draft, the added mass and/or damping. Various alternatives to reduce the heave motion in long-period swells have been in the fore front of research for the last two decades. An alternate hull form of a shape similar to a buoy with deep draft has been proposed in this study. The buoy form Spar is a cylindrical floating vessel with curved surface near the water plane. The present study focus on the efficiency of the buoy form Spar in reducing the heave motion and increasing the heave natural period. A classic Spar of 31 m diameter and deep draft buoy form Spars with 25 and 20 m diameter at the water plane area has been considered. The moon pool diameter of 12.5 m and the displacement of 63, 205 tonnes are maintained for all Spars. The experimental investigations are conducted using 1:100 scale models in the wave flume. The natural period and the damping ratio for the heave and pitch motions were obtained by conducting free decay tests. Numerical simulations have been carried out using panel method. Based on the study, it is concluded that the reduction in water plane area is effective in reducing the hydrodynamic response of the buoy form Spar and increase in the heave natural period is noted.